Analisis Bauran Pemasaran Jasa terhadap Keputusan Pembelian pada Apartemen Tamansari Prospero Sidoarjo - Rizky Eka Febriansah; Dewi Komala Sari; Dina Mayangsari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was done on purpose to help determining the marketing mix for purchasing decisions at the Tamansari Prospero Sidoarjo Apartment.This research is applied method of descriptive research using quantitative. Sampling used is the echnique of Non Probability Sampling through Accidental Sampling and then the samples used was 100 respondents. It also uses techniques of data collection by distributing questionnaires. The data analysis applied is multiple linear regression analysis using SPSS version 25 statistical tools. The variables in this research contains of the independent variable, marketing mix (7P) and the related variable, namely decisions. purchase. The results indicated that the product, price, place, process variables partially have a positive and significant influence toward decision to purchase, but the promotion,people,and physical evidence do not have a significant influence toward decision to purchase the Tamansari Prospero Sidoarjo Apartment. Results Simultaneous research indicates that product, price, place, promotion, people, process and also physical evidence have a positive and significant influence toward purchasing decisions for Tamansari Prospero Sidoarjo Apartments.